Regional Autonomy and Economic Conditions in Indonesia - Ibrahim (ASIAN PUBLISHER, 2023)
This study aims to see the impact of regional autonomy on the economy in Indonesia. There are two variables used to represent the economy, namely economic growth and the unemployment rate. This study uses the literature review method, this is because this method can assist in obtaining a more comprehensive understanding of the concept of regional autonomy and the economy, including theories and concepts. The results of the study show that regional autonomy has a positive impact on the economy in Indonesia, especially being able to increase economic growth and reduce unemployment rates.